2020
DOI: 10.1021/acs.jafc.0c01883
|View full text |Cite
|
Sign up to set email alerts
|

Repressed Gene Expression of Photosynthetic Antenna Proteins Associated with Yellow Leaf Variation as Revealed by Bulked Segregant RNA-seq in Tea Plant Camellia sinensis

Abstract: The young leaves and shoots of albino tea cultivars are usually characterized as having a yellow or pale color, high amino acid, and low catechin. Increasing attention has been paid to albino tea cultivars in recent years because their tea generally shows high umami and reduced astringency. However, the genetic mechanism of yellow-leaf variation in albino tea cultivar has not been elucidated clearly. In this study, bulked segregant RNA-seq (BSR-seq) was performed on bulked yellow- and green-leaf hybrid progeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 61 publications
1
29
0
Order By: Relevance
“…Studies of light harvesting in plants revealed that Lhc family proteins are involved in regulation and distribution of excitation energy between PSI and PSII, in photoprotection as well as in response to various stresses (Singh et al ., 2014; Fristedt et al ., 2015; Gao et al ., 2018). Research on Lhc family proteins in algae, Arabidopsis thaliana and tea, revealed that these proteins play a vital role in plant light protection (Peers et al ., 2009; Adamiec et al ., 2015; Wang et al ., 2020). Therefore, there has been substantial research on Lhc genes, particularly Lhcb2 and Lhcb1 in Arabidopsis (Leoni et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of light harvesting in plants revealed that Lhc family proteins are involved in regulation and distribution of excitation energy between PSI and PSII, in photoprotection as well as in response to various stresses (Singh et al ., 2014; Fristedt et al ., 2015; Gao et al ., 2018). Research on Lhc family proteins in algae, Arabidopsis thaliana and tea, revealed that these proteins play a vital role in plant light protection (Peers et al ., 2009; Adamiec et al ., 2015; Wang et al ., 2020). Therefore, there has been substantial research on Lhc genes, particularly Lhcb2 and Lhcb1 in Arabidopsis (Leoni et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Qubit and Agilent 2100 were used to construct nine RNA library (three tissues × three biological replicates) after filtering of the raw data. The filtering standards included adapter sequence removal via Adapter Removal version 2, quality filtering via the sliding window method, and length filtering via removal of sequences shorter than 50 bp ( Wang et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…A missing assembly of the trimeric LHCII results in no granum formation in the seedling lethal gdc1 mutant (grana-de cient chloroplast 1) [40]. The repressed expression of genes encoding LHCII is correlated with albinism in tea [14]. Without the light-harvesting complex LHCB6, PSII cannot properly organize PSII complexes in the membrane [41], which affects the structure and function of the granum membranes of chloroplasts [42].…”
Section: Low Expression Of Cslhcb6 and Csscy1 May Inhibit Chloroplastmentioning
confidence: 99%
“…The leaf colour changes in albino tea are mainly affected by chloroplast biogenesis and pigment biosynthesis. Numerous genes and signal integrators participate in chloroplast biogenesis [13], suppression of the etioplast-chloroplast transition and damage to grana in the chloroplast [10]; repression of genes encoding LHC [14] and expression of genes during protein processing can cause the leaf colour to change in tea [15]. Leaf colour changes are also largely in uenced by avonoid and carotenoid biosynthesis [16], the phenylpropanoid biosynthesis pathway [17], and the shikimic acid pathway [18].…”
Section: Introductionmentioning
confidence: 99%